The Effects of Forward-Versus Backward-Looking Wage Indexationon Price Stabilization Programs - Crowley, Joe (IMF Working Papers; Working Paper, 1997)
A standard open-economy model is used to show that price stabilization programs are more likely to succeed if labor contracts specify forward-looking wage indexation. Compared with contracts specifying backward-looking wage indexation or wages based on static expectations, such contracts will result in a greater reduction in inflation with lower output costs, smaller misalignment of real wages, smaller outflows of reserves, smaller disruptions caused by policy announcements, and a reduced impact of some shocks during price stabilization programs. These results are generally true whether or not capital is mobile and whether or not expectations are rational.